2019
DOI: 10.1093/ehjcr/ytz215
|View full text |Cite
|
Sign up to set email alerts
|

Isolated left ventricular apical hypoplasia with myocardial non-compaction: a case report

Abstract: Background Isolated left ventricular apical hypoplasia (ILVAH) is a rare congenital cardiac abnormality, which might result in severe symptomatic heart failure (HF) with pulmonary hypertension, atrial fibrillation (AF), or malignant ventricular tachycardia in adults. Case summary A 32-years-old man presented with exertional dyspnoea New York Heart Association Class II and persistent AF. Echocardiography and cardiac magnetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…A recent literature review suggests that aspirin alone is not enough for stroke prevention in these patients [ 2 ]. Two case reports suggest that direct oral anticoagulants (DOACS) may be appropriate as well [ 12 - 13 ], especially given the findings of complete resolution of LV thrombus in non-NCC patients with equal efficacy using DOAC therapy [ 11 , 14 ]. Other studies argue that warfarin is superior to DOACs in preventing embolism in patients with evidence of LV thrombus [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent literature review suggests that aspirin alone is not enough for stroke prevention in these patients [ 2 ]. Two case reports suggest that direct oral anticoagulants (DOACS) may be appropriate as well [ 12 - 13 ], especially given the findings of complete resolution of LV thrombus in non-NCC patients with equal efficacy using DOAC therapy [ 11 , 14 ]. Other studies argue that warfarin is superior to DOACs in preventing embolism in patients with evidence of LV thrombus [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“… 1 Case reports have increased through years with a wide clinical spectrum ranging from asymptomatic children 2 to severely symptomatic adults with associated heart failure (HF), pulmonary hypertension (PH), and malignant tachyarrhythmias. 3 , 4 Hence, we present the first case of ILVAH reported in Peru and Latin America of a young adult who developed some of the aforementioned complications.…”
Section: Introductionmentioning
confidence: 90%
“…57,58 Similarly, several case reports have demonstrated that DOACs could be at least as effective and safe as warfarin in preventing cardioembolic events in NCCM patients. 59,60 Skidan et al reported a case of a 32year-old male with NCCM and isolated LV apical hypoplasia admitted to the hospital for radiofrequency catheter ablation of persistent AF. 60 Despite the high thromboembolic risk due to the concomitant presence of AF and biventricular systolic dysfunction, no thromboembolic events occurred during 2 years of follow-up in NCCM patients receiving long-term oral anticoagulation therapy with Rivaroxaban.…”
Section: Stroke Prevention In Noncompaction Cardiomyopathymentioning
confidence: 99%
“… 57 , 58 Similarly, several case reports have demonstrated that DOACs could be at least as effective and safe as warfarin in preventing cardioembolic events in NCCM patients. 59 , 60 Skidan et al . reported a case of a 32‐year‐old male with NCCM and isolated LV apical hypoplasia admitted to the hospital for radiofrequency catheter ablation of persistent AF.…”
Section: Stroke Prevention In Noncompaction Cardiomyopathymentioning
confidence: 99%
See 1 more Smart Citation